Infection prevention and control: knowledge, practices and associated factors among cleaners at a National Referral Hospital in Uganda - Edwin Kigozi; Livingstone Kamoga; Nelson Ssewante; Patrick Banadda; Faith Atai; Lydia Kabiri; Scovia Nalugo Mbalinda (Elsevier, 2024)
Summary: Background: While most infection prevention and control (IPC) studies focus on healthcare professionals, IPC is everyone's responsibility in any healthcare facility. There is little known about the IPC knowledge among the cleaners who are responsible for housekeeping, environmental cleaning, and waste management within hospitals. This study sought to evaluate the knowledge and practice of IPC among cleaners at Mulago National Referral Hospital (MNRH) to establish a foundation for empowering a strategic workforce that will improve IPC practices within the hospital. Methods: A cross-sectional study was conducted among the cleaners in a national referral hospital in Uganda. The participants were purposively sampled, and data was collected using a web-based, interviewer-administered, questionnaire about IPC knowledge and practices. Results: Of the 120 cleaners recruited, 52.5% were female. Good IPC knowledge was demonstrated in 58.3%, and 30.8% reported good IPC practices. Participants with at least 5 years' work experience had higher knowledge levels (aOR: 10.3, P=0.006, 95% CI: 2-54). Those closely supervised had lower IPC knowledge compared with those with less supervision. Participants with fixed work schedules (aOR: 0.2, P=0.028, 95%CI: 0-0.8), were less likely to exhibit good IPC practices. In addition, 63.1% were knowledgeable about waste segregation, recognising bin colours and the correct disposal of sharps and needles. Despite good compliance with personal protective equipment, poor hand-washing practices were reported. A positive correlation between knowledge and practice scores was established. Conclusion: Hospital cleaners in a national referral hospital in Uganda IPC reported poor infection prevention practices despite good knowledge. For IPC knowledge and practice to correlate positively, ongoing practical training is vital to maintain knowledge and good practice to establish a successful IPC program.